Impact of COVID-19 on the Postoperative Bariatric Surgery Patient Experience. Issue 4 (6th April 2023) - Murtha, Jacqueline A.; Alagoz, Esra; Breuer, Catherine R.; Eierman, Lindsey; Jawara, Dawda; Farrar-Edwards, Dorothy; Voils, Corrine I.; Funk, Luke M.
Abstract : Objective: To characterize patient and provider perceptions of the impact of coronavirus disease 2019 (COVID-19) on weight loss following bariatric surgery. Background: COVID-19 has disrupted routines and healthcare throughout the United States, but its impact on bariatric surgery patients' postoperative experience is unknown. Methods: Semistructured interviews with bariatric surgery patients, primary care providers, and health psychologists were conducted from April to November 2020. As part of a secondary analysis, patients and providers described how the COVID-19 pandemic affected the postoperative experience within 3 domains: dietary habits, physical activity, and follow-up care. Interview guides were created from 2 conceptual models: Torain's Surgical Disparities Model and Andersen's Behavioral Model of Health Services Use. Study team members derived codes, which were grouped into themes using conventional content analysis. Results: Thirty-four participants were interviewed: 24 patients (12 Roux-en-Y gastric bypass and 12 sleeve gastrectomy), 6 primary care providers, and 4 health psychologists. Patients were predominately female (83%) and White (79%). Providers were predominately female (90%) and White (100%). COVID-19 affected the postoperative bariatric surgery patient experience via 3 mechanisms: (1) it disrupted dietary and physical activity routines due to facility closures and fear of COVID-19 exposure; (2) it required patients to transition their follow-up care to telemedicine delivery; and (3) it increased stress due to financial and psychosocial challenges. Conclusions: COVID-19 has exacerbated patient vulnerability. The pandemic is not over, thus bariatric surgery patients need ongoing support to access mental health professionals, develop new physical activity routines, and counteract increased food insecurity.